Penyuluhan Fisioterapi Mengenai Posisi Duduk Yang Benar pada Siswa SMP Diponegoro Tumpang - Ummah, Salma Nurul; Hasta, Arys; Febriani, Ninien (LPPM IT Telkom Purwokerto, 2025)
Back pain is increasingly common in adolescents, including junior high school students, mainly due to the habit of sitting for long periods in non-ergonomic positions. Sitting in an unergonomic posture can put excessive pressure on the spine and cause muscle imbalances, triggering back pain. Counseling is carried out as a preventive measure to reduce the risk of back pain due to the habit of sitting for long periods in the wrong position. Counseling was carried out on students of Diponegoro Tumpang Junior High School using the Participatory Action Research (PAR) method involving students as active participants and physiotherapy students as speakers. The activity was carried out by providing a pre-test and post-test, each consisting of 5 questions to evaluate the level of student understanding of the topic. The results of the counseling showed that the students' post-test scores regarding their understanding of the topic presented increased, compared to the scores during the pre-test. This shows that the counseling that was carried out has increased students' understanding so that it is hoped that students will be more concerned with good sitting positions to prevent back pain.